Can sustainable urban planning determine people’s happiness and well-being? - Baschera, Weligton Lucas; Hahn, Ivanete Schneider (Revista de Administração da UFSM, 2022)
Purpose – This study was designed to present how urban planning is associated with, and explain psychological well-being, health, time use, education, cultural diversity and resilience, community vitality, good governance, ecological diversity, resilience, and living standards. We used Gross National Happiness Index (GNH) as theoretical background. Design/methodology/approach – Quantitative and explanatory research was conducted and operationalized through a survey of 212 citizens. We used data from a mid-sized city, inner Santa Catarina state, Brazil. Findings – The linear regression showed that urban planning predicts happiness and well-being. More specifically, urban planning impacts more time use perception; community vitality; ecological diversity and resilience; and most important, living standards. Research implications – we found that urban planning impacts more on the variables that are directly related to the environment, explained by the pillars of sustainable socio-economic development and environmental conservation. The individual and psychological dimensions related to health, culture, and education don't show the same impact, as well as good governance. Originality/value: a potential study to be used by government agencies to act directly in the elaboration of public policies once it is understood that using the GNH can identify specific deficits.